CARBONATE RESERVOIR CHARACTERIZATION USING EXTENDED ELASTIC IMPEDANCE INVERSION METHOD OF KUJUNG-1 FORMATION, âSISâ FIELD, EAST JAVA BASIN - As Shiddiq, Irghan
The "SIS" field is an oil and gas producing field located in the East Java Basin. One of the potential reservoirs in the East Java Basin is the Kujung formation which is composed of carbonate rocks with shale interspersed. The formation that is the main focus in this study is the Kujung-1 formation because of its good characteristics and features based on the petroleum system. This study aims to characterize carbonate reservoirs and identify the distribution of rocks that have the potential as reservoirs. To be able to do this, sensitive elastic parameters and appropriate seismic method are needed in order to give good separation of the lithology and presence of hydrocarbon fluid in the carbonate reservoir. The data are well data and partial angle stack seismic data. Based on sensitivity analysis, the Mu-Rho parameter is the most sensitive parameter to distinguish lithology and Lambda-Rho is the most sensitive parameter to distinguish fluid. These two parameters will be used in the Extended Elastic Impedance (EEI) inversion method to obtain the optimal correlation angle (?) with the elastic parameters Mu-Rho and Lambda-Rho. The two-term AVO Ursenbach-Stewart (2008) equation is used to generate volumes of P-wave reflectivity (????????) and S-wave reflectivity (????????). After that, the EEI reflectivity (REEI) was made from ???????? and ???????? which was rotated based on the optimal correlation angle (?) of EEI with the elastic parameters of Mu-Rho and Lambda-Rho. REEI is inverted using Linear Programming Sparse-Spike. The potential reservoir in the Kujung-1 formation is porous carbonate with a Mu-Rho value below 20 GPa g/cc. Porous carbonate filled with hydrocarbon with a Lambda-Rho value below 20 GPa g/cc and spread over high areas.